2016
DOI: 10.1093/jnci/djw121
|View full text |Cite
|
Sign up to set email alerts
|

De Novo vs Nevus-Associated Melanomas: Differences in Associations With Prognostic Indicators and Survival

Abstract: These data suggest that de novo melanomas are more aggressive than nevus-associated melanomas. This classification scheme may also provide a useful framework for investigations into sex differences in melanoma outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 42 publications
5
76
1
Order By: Relevance
“…Gymerman et al . also reported de novo melanomas were associated with stages greater than stage I [18]. Relatedly, the current study found that nevus-associated melanomas were associated with early stages and tended to have less positive sentinel lymph nodes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Gymerman et al . also reported de novo melanomas were associated with stages greater than stage I [18]. Relatedly, the current study found that nevus-associated melanomas were associated with early stages and tended to have less positive sentinel lymph nodes.…”
Section: Discussionsupporting
confidence: 67%
“…The risk factors of ALMs include mechanical stress, penetrative injury, heavy exposure to agricultural chemicals, and ethnicity [1416]. The mean Breslow thickness of all the melanomas in this investigation was 3.7 mm, which was much thicker than the thicknesses reported in previous reviews of Caucasian patients, suggesting that melanomas tend to have greater thickness in Asian patients [17, 18]. Although over half of all melanomas in Asians are ALMs, ALMs account for only 3–10% of all melanoma patients among Caucasians [1922].…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have also found that nodular melanomas are less likely than other subtypes to be associated with a pre‐existing naevus 6 , 9 , 12 , 16 , 17 , 19 . A recent cross‐sectional study in Brazil found that 8.7% of nodular melanomas were associated with a benign naevus 14 .…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, other studies have shown that histological naevus association confers a survival benefit over melanomas that arise de novo . 5 However, in Cymerman et al .’ s large prospective study , de novo melanoma classification remained an independent predictor of poorer survival compared with naevus‐associated melanomas in only one of two cohorts . Sheen et al .…”
Section: Patient Demographics and Tumour Characteristics Of Naevus‐asmentioning
confidence: 97%
“…The studies that have compared survival outcomes between naevus-associated and de novo melanomas have produced conflicting results. [3][4][5][6] Superficial spreading melanoma (SSM) and nodular melanoma (NM) together account for approximately 70% of all invasive melanomas and represent the most common radial and vertical growth phase melanoma subtypes. Therefore, the aim of this study was to determine the prognosis of naevus-associated and de novo melanoma in these two melanoma subtypes.…”
mentioning
confidence: 99%